2021
DOI: 10.3897/subtbiol.39.65305
|View full text |Cite
|
Sign up to set email alerts
|

Chaimowiczia: a new Iuiuniscinae genus from Brazil (Oniscidea, Synocheta, Styloniscidae) with the description of two new troglobitic species

Abstract: A new genus of Styloniscidae, Chaimowicziagen. nov., is described with two new species: Chaimowiczia tatussp. nov. from Gruta do Padre cave (Santana, Bahia) and Chaimowiczia uaisp. nov. from Lapa d’água do Zezé cave (Itacarambi, Minas Gerais). The new genus and species were allocated into the subfamily Iuiuniscinae, hitherto monotypic, by the pronounced rectangular-shaped lateral pereonites epimera, dorsal surface smooth, body outline continuous without a gap between pereon and pleon, and pleonites 3 to 5 deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…nov. also exhibits well-developed epimera on the pereonites and pleonites 3-5, as on the other two congeneric species C. uai and C. tatus. Cardoso et al (2021) hypothesized that such morphology could be related to a "ghost predation in the past" in a period when the ancestor populations could be under a predator selective pressure. However, this hypothesis still needs further studies in order to be confirmed (or refuted).…”
Section: Habitat and Ecological Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…nov. also exhibits well-developed epimera on the pereonites and pleonites 3-5, as on the other two congeneric species C. uai and C. tatus. Cardoso et al (2021) hypothesized that such morphology could be related to a "ghost predation in the past" in a period when the ancestor populations could be under a predator selective pressure. However, this hypothesis still needs further studies in order to be confirmed (or refuted).…”
Section: Habitat and Ecological Remarksmentioning
confidence: 99%
“…Chaimowiczia Cardoso, Bastos-Pereira, Souza & Ferreira, 2021 consists in a recently described genus for the subfamily Iuiuniscinae (Styloniscidae) (Cardoso et al 2021). The species allocated into the new genus presented the antenna flagellum with three articles; rectangular-shaped lateral pereonites epimera not apically acute and apex of pleopod 2 endopod with an acute tip and an acute or rounded lobe directed outwards (Cardoso et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, about 210 species are known from Brazil, 70 of which, belonging to the families Styloniscidae, Philosciidae, Scleropactidae, Dubioniscidae, Platyarthridae, Porcellionidae, Armadillidae, Pudeoniscidae, and Armadillidiidae, are recorded from Brazilian caves. Thirty-two taxa are considered to be troglobites (obligatory and restricted to caves), several are troglophiles (facultative cave species), and some species are possibly trogloxenes (Souza et al 2011;Campos-Filho et al 2014, 2015a, 2015b, 2016, 2017a, 2017b, 2018Bastos-Pereira et al 2017;Fernandes et al 2018Fernandes et al , 2019Cardoso et al 2020aCardoso et al , 2020bCardoso et al , 2021. The species placed into the last two categories are difficult to assign into a correct subterranean category due to the scarcity of distribution data outside caves.…”
Section: Introductionmentioning
confidence: 99%
“…Among the troglobitic representatives of the Brazilian Oniscidea, 12 species have an amphibious way of life, all in the Styloniscidae: Chaimowiczia uai Cardoso, Bastos-Pereira, Souza & Ferreira, 2021, C. tatus Cardoso, Bastos-Pereira, Souza & Ferreira, 2021, Iuiuniscus iuiuensis Souza, Ferreira & Senna, 2015, Spelunconiscus castroi Campos-Filho, Araujo & Taiti, 2014, Xangoniscus aganju Campos-Filho, Araujo & Taiti, 2014, X. ceci Cardoso, Bastos-Pereira, Souza & Ferreira, 2020, X. dagua Cardoso, Bastos-Pereira, Souza & Ferreira, 2020, X. ibiracatuensis Cardoso, Bastos-Pereira, Souza & Ferreira, 2020, X. itacarambiensis Bastos-Pereira, Souza & Ferreira, 2017, X. lundi Cardoso, Bastos-Pereira, Souza & Ferreira, 2020, X. odara Campos-Filho, Bichuette & Taiti, 2016, and X. santinhoi Cardoso, Bastos-Pereira, Souza & Ferreira, 2020 The present work describes two new species of Xangoniscus from the Serra do Ramalho karst area, state of Bahia, both occurring in special microhabitats, namely the upper aquifers fed by infiltration of water in the limestone rock. Moreover, aspects of their ecology and natural history, as well as conservation remarks about this particular and unique fauna and the region of Serra do Ramalho are given.…”
Section: Introductionmentioning
confidence: 99%